Infodemic, social contagion and the public health response to COVID-19: insights and lessons from Nigeria. (3rd July 2022) - Alichie, Bridget O.; Ediomo-Ubong, Nelson; Onyima, Blessing Nonye
ABSTRACT: Background: The expansion of the internet and social media platforms have spurred an online infodemic, which has surged towards alarming proportions across the globe. The online infodemic trend has been particularly felt in Nigeria in the area of health information and communication throughout the recurring public health emergencies of the current decade. The outbreak of the ongoing COVID-19 (SARS-CoV-2) pandemic in March 2020 reaffirms the biggest threat of infodemic across online platforms against containment efforts and responses in Nigeria. Methods: This study reflects on infodemic trends related to COVID-19 in light of previous zoonotic viral diseases in Nigeria (e.g. Ebola, Lassa, and Monkeypox). Relevant published research and gray literature on zoonotic diseases and communication responses are reviewed. Results: Drawing lessons and insights from previous zoonotic viral diseases in Nigeria, we show the extent to which online infodemic hampers public health responses to the COVID-19 pandemic. The theory of social contagion, which describes the fear and panic that emerge during disease outbreaks, is deployed to deepen understanding of how online infodemic pose threats during health emergencies. Conclusion: We argue that Nigeria and other countries affected by disease outbreaks would thrive better by proactive inclusion and management of online communication channels in addition to coordinated clinical (prophylactic or therapeutic) models.